Satisfaction and Loyalty: An Analysis of Halal Tourism in Minority Muslim Destinations - Ayu, Beta Sukma; Istyakara Muslichah (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the relationship between tourist satisfaction and loyalty, emphasizing the role of the halal experience in shaping attraction experience, perceived value, and tourist behavior. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS, data from 196 Muslim tourists in Bali were analyzed. The results indicate that the halal experience significantly influences attraction experience, perceived value, and satisfaction. Attraction experience positively impacts perceived value and satisfaction, while perceived value enhances both satisfaction and loyalty. Additionally, tourist satisfaction is a key driver of loyalty. This study contributes to the literature by exploring halal tourism’s impact on loyalty in Bali, offering insights for refining research models and expanding study scopes. Practical implications benefit the Bali regional government, tourism stakeholders, and marketing managers in halal destinations, helping develop targeted attraction-based strategies to strengthen Bali’s position as a premier halal tourism destination and attract more Muslim tourists.